Cardiac vagal afferent neurotransmission in health and disease: review and knowledge gaps - van Weperen, Valerie Y. H.; Vaseghi, Marmar (Frontiers in Neuroscience, 2023)
The meticulous control of cardiac sympathetic and parasympathetic tone regulates all facets of cardiac function. This precise calibration of cardiac efferent innervation is dependent on sensory information that is relayed from the heart to the central nervous system. The vagus nerve, which contains vagal cardiac afferent fibers, carries sensory information to the brainstem. Vagal afferent signaling has been predominantly shown to increase parasympathetic efferent response and vagal tone. However, cardiac vagal afferent signaling appears to change after cardiac injury, though much remains unknown. Even though subsequent cardiac autonomic imbalance is characterized by sympathoexcitation and parasympathetic dysfunction, it remains unclear if, and to what extent, vagal afferent dysfunction is involved in the development of vagal withdrawal. This review aims to summarize the current understanding of cardiac vagal afferent signaling under in health and in the setting of cardiovascular disease, especially after myocardial infarction, and to highlight the knowledge gaps that remain to be addressed.